Exploration of apathy in people living with neurocognitive disorder - Burgon, Clare (2023)
Background Apathy is highly prevalent in people living with neurocognitive disorder (NCD). What constitutes apathy and how it is experienced by people living with NCD is poorly understood and under-researched, and there are no gold-standard measures of apathy. Apathy is associated with impaired functional ability, worse quality of life, conversion from MCI to dementia, increased care costs and carer burden, and may prevent effective participation in therapy programmes. It is important to understand what constitutes apathy, how to assess it, and identify possible mechanisms for apathy and potential treatment targets, in people living with NCD. However, the typical domain-based approach may be limiting our understanding of apathy. It is important to explore how individual indicators of apathy relate to one another. A broader exploratory approach is needed to understand how to conceptualise apathy, identify possible mechanisms of apathy, including an examination of how apathy is understood and experienced in people living with NCD. This thesis aimed to answer the following research questions: What measures of apathy are available and what is the quality of the evidence for their use with people living with NCD?; How should apathy be characterised and what are its conceptual boundaries?; What are the mechanisms and impact of apathy?